The importance of islamic business ethics in increasing consumer loyalty to cooking oil product - Norikun, Bun (Indonesian Journal of Islamic Economics Research, 2025)
This research is motivated by a series of alleged fraud cases related to subsidized cooking oil, including reduced packaging volumes, sales above the highest retail price, and alleged corruption at Minyakita. These cases will impact consumer trust in cooking oil brands and, consequently, consumer loyalty. This study was conducted to determine how the dimensions of Islamic business ethics, consumer behavior, and customer satisfaction influence consumer loyalty to Minyakita brand cooking oil products. The sampling technique used purposive sampling with 112 respondents. The analysis used was Structural Equation Modeling (SEM). The conclusion of this study is that Islamic business ethics has a significant effect on consumer behavior, Islamic business ethics does not have a significant effect on consumer loyalty, Islamic business ethics has a significant effect on customer satisfaction, consumer behavior has a significant effect on customer satisfaction, consumer behavior does not have a significant effect on consumer loyalty, customer satisfaction has a significant effect on consumer loyalty. The mediating variables, namely consumer behavior and customer satisfaction, have a very strong influence on the contribution between Islamic business ethics and consumer loyalty.